Pengaruh Kegiatan Origami Kertas Washi Terhadap Kreativitas Anak Di Taman Kanak–Kanak Aisyiah No. 1 Muara Panas Kabupaten Solok - Mutiatul Husna; Rismareni Pransiska; Yulsyofriend Yulsyofriend (Universitas Bengkulu, 2019)
The research aim of this study is determine The Influence Of Washi Paper Origami Activities On The Of Children At Kindergarten Aisyiah No.1 Muara Panas Kabupaten Solok The research method used is quantitative approach, this research is quasi experimental design using Washi Paper and control class using conventional media.The collecting data technique was test and the instrument used to collecting data was declaration sheet. Then the data processed by doing t-test. Based on the calculation of t-test obtained that arithmetic greater than t tables shows that there is a significant influence on the Paper Washi Of Creativity Of Children. Thus it can be concluded that I washi paper Origami influences the of children’s creativity at Kindergaten Aisyiah no. 1 Muara Panas Kabupaten Solok.